TOTAL QUALITY MANAGEMENT SEBAGAI STANDAR MUTU PRODUK - MOH. NASIKH (STIE Indonesia Malang, 2018)
Researcher (it means I) is interested in studying this journal to describe about important and updating issuesfor improving products or services also increasing total quality management (TQM) and discussing about how to market our products or services to be accepted by customers or consumers (customer focus). For the time being, I am very interested to discuss some ways that can be used to multiply or increase our sales or our profit by using planning, controlling (inspection)and quality assurance and products or services improvement from raw material (input) until finished goods (output), and finally can be marketed to consumers (customers) or accepted by them with continuously repurchasing and also how to promote our products or services to them by using total quality management (TQM) or integrated quality management.Beside that, I am also interested in discussing momentary issues, such as: cycle of product development, safety of products or services, the products or servivesthat not get along with prime standards, correlation with some supliers, and about education and training for employees, also issues of ethics. So, in the prospect, our products or services are able to overcome the market-share, because they are so very competitive ones (market-based competition) and very sustainable thing.Keywords: Total Quality Management,Cyccle of Product Development, Product Quality